2016
DOI: 10.1002/2016gc006536
|View full text |Cite
|
Sign up to set email alerts
|

The role of symbiotic algae in the formation of the coral polyp skeleton: 3-D morphological study based on X-ray microcomputed tomography

Abstract: Symbiotic algae of primary polyps play an important role in calcification of coral skeletons. However, the function of the symbiotic algae, including the way they influence the physical features of their host skeleton under various conditions, is not well understood. We used X‐ray microcomputed tomography to observe skeletal shape characteristics in symbiotic and aposymbiotic primary polyps of Acropora digitifera that were cultured at various temperature and pCO2 levels (temperature 27, 29, 33°C; pCO2 400, 800… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The second calcification step, in which aragonite is precipitated, appears to differ, depending on whether zooxanthellae are present or not. Iwasaki et al (2016) measured the shapes of skeletons of polyps with and without symbionts prepared in the same way as for the experiments in this study by X-ray micro-CT scanning. They found that symbiotic primary polyps had well-developed folding margins, unlike asymbiotic ones, and their skeletons were also higher.…”
Section: Calcification Mechanism Related To Photosynthesismentioning
confidence: 99%
“…The second calcification step, in which aragonite is precipitated, appears to differ, depending on whether zooxanthellae are present or not. Iwasaki et al (2016) measured the shapes of skeletons of polyps with and without symbionts prepared in the same way as for the experiments in this study by X-ray micro-CT scanning. They found that symbiotic primary polyps had well-developed folding margins, unlike asymbiotic ones, and their skeletons were also higher.…”
Section: Calcification Mechanism Related To Photosynthesismentioning
confidence: 99%
“…In recent years, computed tomography (CT) has been applied to study reef‐building coral skeletons (Beuck et al, 2007 ; Gutiérrez‐Heredia et al, 2015 ; Knackstedt et al, 2006 ; Kruszyński et al, 2007 ; Kruszynski et al, 2006 ; Pinzón et al, 2014 ). With the development and popularization of high‐resolution micro‐computed tomography (HRCT), research on coral skeletons has revealed the morphological and internal structures of coral branchlets, and also investigated coral skeletal structures (Ivankina et al, 2020 ; Sentoku et al, 2015 ; Sentoku et al, 2015 ; Urushihara et al, 2016 ) and exogenous influences on coral skeletons, including water currents (Chindapol et al, 2013 ), the marine environment (Iwasaki et al, 2016 ), and ocean acidification (Enochs et al, 2016 ; Fordyce et al, 2020 ). However, there are various challenges in studying coral growth patterns regulation using CT sectional slices that are singly dependent on skeleton reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the geochemical methods, culture experiments should be conducted and molecular biological methods should be applied to clarify the biological mechanism of calcification. Recent papers have recognized that coral primary polyps are particularly suitable for biomineralization studies because of their small size and simple form (Iwasaki et al 2016;Ohno et al 2017). An integrated approach that brings various perspectives to bear on these problems is needed, because coral biomineralization reflects synergetic effects (Fig.…”
Section: Future Directionsmentioning
confidence: 99%